Millennial Farmer Strategies in Horticultural Entrepreneurship - Wirrdiana Yuniasih, Annisa; Rahman, Natasya; Nurlaela, Siti (Publisher Cv. Inara, 2023)
Indonesia has abundant agricultural resources and great potential in agricultural development. The existence of these agricultural resources has not been matched by the low regeneration of millennial farmers. The Ministry of Agriculture of the Republic of Indonesia through the Agriculture and Food Security Service of Gunungkidul Regency projects a Horticulture Village program to be implemented in Karangrejek Village, Kapanewon Wonosari. This program encourages millennial farmers who have their own innovations and strategies in agricultural development, especially in running farming in the horticulture sector. This paper aims to find out the strategies and innovations carried out by millennial farmers in running farming in the horticulture sector. The millennial farmer strategy is carried out when cultivating and marketing horticultural products, especially shallots and chilies. The strategies carried out in the cultivation aspect are: planting with the intercropping method, off season farming, selection of superior seeds, use of biological control agents, and use of high beds. On the marketing aspect of the results: digital media marketing, post-harvest packaging. The characteristics of millennial farmers in dealing with entrepreneurial problems are: never give up, keep trying, innovate and stay afloat in horticultural farming.